(untitled) (Journal of the College of Education for Women, 2019)
The language of theatre is made by a number of physical tools and moral elements. So as the actors, costumes, lightings and accessories represent the physical aspects of the show, they also represent its moral aspect too. When they transform from plastic words in the space of the visual show to become signs carrying its indications that give the meaning through the link, overlap and arrangement of its movements so as to finally look like as wording in a sentence carries the meaning and represent the language of theatre speech.The show usually sends the recipient continuous signs that go beyond the limits of expressions that are conveyed by these tools, and that cover the largest part of the meaning. So what is kept hidden or unannounced, which is called the (Untold Story) in literature, is known as a constant image that reaches to the recipient and all of a sudden it goes away and proceeds. Every attempt that the recipient tries to take would add one segment to the whole meaning structure that the show is drawing. Therefore, what is the frames and limits of the untold story in the language of theatre..? and what is its aesthetic dimensions..?The researcher chooses "Insu Herostrat" as a sample to apply what is given in the theoretical chapter of the study. The most important results that the researcher has come up with are that the untold story in the language of theatre draws the attention of the recipient to the meaning of the dramatic conflict and its stylistic forms and aesthetic aspects, and so achieving the most significant springs of the aesthetic structure that are made by the datum of the untold story in the language of theatre.